2014
DOI: 10.1080/87565641.2014.940619
|View full text |Cite
|
Sign up to set email alerts
|

MR Spectroscopic Evidence of Brain Injury in the Non-Diagnosed Collision Sport Athlete

Abstract: With growing evidence of long-term neurological damage in individuals enduring repetitive head trauma, it is critical to detect lower-level damage accumulation for the early diagnosis of injury in at-risk populations. Proton magnetic resonance spectroscopic scans of the dorsolateral prefrontal cortex and primary motor cortex were collected from high school American (gridiron) football athletes, prior to and during their competition seasons. Although no concussions were diagnosed, significant metabolic deviatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
77
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(87 citation statements)
references
References 47 publications
5
77
5
Order By: Relevance
“…These findings strongly suggest an additive effect of injury during a time of vulnerability. An additive effect of injury may also affect non--diagnosed players remaining in play, as supported by a recent 1 H MRS study (Poole et al, 2014).…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…These findings strongly suggest an additive effect of injury during a time of vulnerability. An additive effect of injury may also affect non--diagnosed players remaining in play, as supported by a recent 1 H MRS study (Poole et al, 2014).…”
Section: Introductionmentioning
confidence: 69%
“…Additional details on ROI selection, data collection, and procedures may be found in Poole et al (2014).…”
Section: Mr Spectroscopymentioning
confidence: 99%
“…2,11,44,61,100 The issue relating to the effects of subconcussive impacts is controversial as researchers and clinicians are divided on the true effects. 4,40,44,67,74,103 Some research 74 has reported that these impacts have minimal effect on cognitive functions, while others 4,40,67,89,103 have reported these to be detrimental to cerebral and cognitive functions. To date, there is a paucity of evidence to identify the impact acceleration that is adequate to produce a non-structural brain injury associated with the neuronal changes of concussion.…”
Section: Impact Thresholdmentioning
confidence: 99%
“…It has been suggested 100, 103 that brain injuries not only come from concussive events but also from the accrual of subconcussive impacts that can result in pathophysiological changes in the brain. There are numerous studies 2,4,35,40,67,89,103 published that have demonstrated that the accumulation of subconcussive blows can result in neurophysiological changes. However, similar to the literature focused on concussion and mild traumatic brain injury (mTBI), the literature on subconcussive head trauma is limited.…”
Section: Introductionmentioning
confidence: 99%
“…190 In younger (high school) athletes, increased glutamate and glutamine levels were detected by MRS at post-season versus preseason evaluation, even in players who had not experienced clinically significant concussion during the season. 191 Such findings suggest that even subconcussive head impacts can result in the activation of glutamate pathways, implying cellular injury or neuronal death, despite the absence of symptoms. Levels of creatinine and myoinositol (an organic osmolyte located in astrocytes 192,193 ) were also significantly altered in a subset of the participants in the aforementioned study.…”
Section: Fluid-based Biomarkersmentioning
confidence: 99%